ABO blood groups and SARS-CoV-2 susceptibility - Stowell, Sean (Henry Stewart Talks, 2021)
How blood group can affect susceptibility to viruses, The initial studies into blood group and COVID-19 susceptibility, Molecular research in this topic, The possible involvement of the Rhesus (Rh) protein, Future steps in this field